Afrofuturismo: temporalidade, ancestralidade e tecnologia na construção de subjetividades negras - Tszesnioski, Roberta Reis Bahia (2023)
This thesis examines Afrofuturist literary representations present in the novels Kindred - Laços de Sangue, by the American writer Octávia Butler, Sankofia: breves histórias sobre o afrofuturismo by the writer Luciene Marcelino Ernesto, better known as Lu Ain-Zaila, and Caçador Cibernético da Rua 13 and A cientista guerreira do Facão Furioso, by Fábio Kabral. Afrofuturism is an artistic, aesthetic, political and cultural movement that arises from the encounter between technology and science fiction, which intertwine with the issues of diaspora, slavery and racism experienced by blacks in the midst of modernity. This movement manifests itself through literature, cinema, fashion, arts, music, etc. It can be said that Afrofuturist artists, in addition to wanting to tell good science fiction narratives, seek out black stories that have been erased by a Eurocentric vision. Understanding that these stories bring the trajectory of a people, their ancestry, their identity, their religiosity, etc., Afrofuturism, by recovering this essence, takes us to the dimension of understanding and accepting our blackness and everything that it represents, which is a new vision of society, but also the construction of new and better black futures, breaking with the yoke of marginalization. Furthermore, the novels examined, in addition to bringing narratives that trace back the suffering that Africans were subjected to with enslavement and consequently with colonization in Africa, praise the traditions, culture, religion, science and technology produced by Africans and that extended in the diaspora with new cultural formations, functioning as a counter-narrative of the epistemic discourses produced about Africa, Africans and their descendants. In this way, we understand that the analyzed novels and short stories, within each proposed approach, allow us to understand the importance of (re) building blacksubjectivities and identities, which will permeate ancestral knowledge in order to propose redirecting our gaze to History from a perspective Afrocentric, where black men and women are protagonists of their narratives, expressions and manifestations.